The 2010s—Genealogies of Religion, Twenty Years On: An Interview with Talal Asad - Martin, Craig; Asad, Talal (Bulletin for the Study of Religion, 2022)
For most of its history, the Bulletin has provided a conversational space for sitting with provocative thinkers who have helped scholars reimagine the possibilities of what we do in the field. To commemorate our fiftieth anniversary, we have reprinted a popular exchange between former-Bulletin editor and now-Bulletin advisory board member, Craig Martin and anthropologist Talal Asad. The following conversation comes from Bulletin 43.1 (2014):